Synthesis of Bis{meso-Tetrakis(4-N-alkylpyridiniumyl)porphyrinato}cerium and Its Redox Switching Behavior - Toshio Nishino; Yasuyuki Yamada; Ayumi Yamamoto; Kentaro Tanaka (Molecules, 2021)
A novel double-decker porphyrin complex, bis{meso-tetrakis(4-N-alkylpyridiniumyl)porphyrinato}cerium, was prepared. Electrochemical measurements revealed that this complex exhibited reversible redox waves corresponding to a 1e– redox reaction of the cerium center. Treating the complex alternately with an oxidant and a reductant resulted in the reversible redox switching between the oxidized and reduced states in an organic solvent.